Indirect model predictive control strategy with active damping implementation for a direct matrix converter operating at fixed switching frequency - Rivera, Marco; Dan, H.; Tarisciotti, Luca; Wheeler, Patrick (2017)
One of the main drawbacks of the implementation of predictive control in a direct matrix converter is the high com¬putational cost and the adequate selection of weighting factors in order to control both input and output sides. In this paper is proposed an indirect model predictive current control strategy enhanced with a fixed switching predictive strategy and an active damping implementation. With all this, the idea is to reduce the computational cost while eliminating the necessity of weighting factors and improving the performance of the full system. The proposed method is based on the fictitious dc-link concept, which has been used in the past for the classical modulation and control techniques of the direct matrix converter. Simulated results confirm the feasibility of the proposal demonstrating that it is an alternative method to classical predictive control strategies for the direct matrix converter.